Anthropometric and cardiovascular variables of elite athletes - Kyselovicová, O.; Labudová, J.; Zemková, E.; Cierna, D.; Jelen, M. (Acta Facultatis Educationis Physicae Universitatis Comenianae, 2016)
Synchronized swimming and aerobic gymnastics are competitive sports that have grown in popularity throughout the Slovakia and around the world. Unfortunately, a paucity of research exists either on anthropometric and physiological characteristics or physical benefits of these sports. The present study examined anthropometric and cardiovascular characteristics of control group - CO (n = 10) in comparison to competitive synchronized swimmers - SS (n = 11) and aerobic gymnasts - AG (n = 10) between the ages of 13 and 25 years. The physical measures were assessed per the protocols in the following order: height (BH), weight (BW), body mass index (BMI), and % body fat (% BF). The measurements of maximal oxygen consumption (VO2max) and maximum heart rate (HRmax) were examined by spiroergometry via COSMED K4b2. All measurements were collected by trained data collection staff. An analysis of variance (Kruskal - Wallis) with a Mann-Whitney U test for the significant effect among the three groups showed that aerobic gymnasts were taller than synchronized swimmers and control group (p = .02). Training and conditioning requirements specific for the two athletic groups caused that AG and SS have higher level of VO2max (p = .02) and VO2max.kg-1 (p = .00), and also lower level of the body weight (p= .01), BMI (p = .01) and the % BF (p = .00). These findings confirm that selected parameters are considered the bases for success in elite sports. This information could also help to design specific training and evaluate the adaptation to training stimuli with the aim to maximize sport performance.